An Advanced Intelligent Tourist Guide - Joshi, RH; Deshpande, BD; Gohane, DM; Gautam, RS (International Journal of Computer Sciences and Engineering, 2020)
A recommendation system is more important and helpful in both research and industry. This paper first examines the method of travel sequence recommendation. The proposed methodology is to design a system based on user’s point of interests. The whole procedure comprise of following: Pages are accessible to the users based on Google API. Based on the point of interest, all the results are retrieved. The proposed methodology is implemented using Google API keys to find places according to user’s point of interests. Three places API used here are place search, place text search and place details API. The technique is tried on self-made database comprising of user information, user’s feedback, country, state and city, spot and spot types. In this website, user can give feedback for the previously visited places.